Dimensional structure regulation of organic–inorganic hybrid perovskite and its application in thin film transistors. (7th July 2021) - Guo, Ning; Li, Juan; Yang, Shang; Zhang, Jianjun; Ni, Jian; Cai, Hongkun
Abstract: The effects of dimensional structure on the properties of lead iodide perovskite (C8 H9 NH3 )2 (CH3 NH3 ) n −1 Pb n I3 n +1 were investigated. Furthermore, perovskite thin films with different dimensionalities were applied as the channel layer of thin film transistors (TFT). The electrical performance and stability of TFT devices were significantly improved through the regulation of dimensional microstructure of the perovskites. As a result, the quasi-2D ( n  = 6) perovskite TFTs achieved a field-effect mobility ( μ FE ) of 3.90 cm 2 V −1 s −1, with 10 4 on-off current ratio and −1.85 V threshold voltage, which can be maintained well after 4 days without degradation at 30% ambient humidity. Moreover, the electrical performance of the TFTs based on Pure-2D and Quasi-2D perovskite also exhibited a good bias stability.